Implicit and explicit knowledge in second language learning, testing and teaching - Ellis, Rod 1944-; Loewen, Shawn 1966-; Elder, Catherine; Erlam, Rosemary; Philp, Jenefer ca. 20./21. Jh; Reinders, Hayo (Multilingual Matters, 2009)
The implicit/ explicit distinction is central to our understanding of the nature of L2 acquisition. This book begins with an account of how this distinction applies to L2 learning, knowledge and instruction. It then reports a series of studies describing the development of a battery of tests providing relatively discrete measurements of L2 explicit/ implicit knowledge. These tests were then utilized to examine a number of key issues in SLA - the learning difficulty of different grammatical structures, the role of L2 implicit/ explicit knowledge in language proficiency, the relationship between learning experiences and learners’ language knowledge profiles, the metalinguistic knowledge of teacher trainees and the effects of different types of form-focused instruction on L2 acquisition. The book concludes with a consideration of how the tests can be further developed and applied in the study of L2 acquisition
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Jul 2018)
Keywords: explicit knowledge; explicit/implicit knowledge; foreign language learning; implicit knowledge; L2 acquisition; L2 instruction; L2 teaching; language learning; language proficiency; language teaching; language testing; learning grammar; Second Language Acquisition; SLA.; teaching grammar; Language and languages -- Study and teaching; Second language acquisition; Sprachtest; Fremdsprachenlernen; Implizites Wissen; Aufsatzsammlung